Maprani Sebagai Rangkaian Pada Ngusabha Kadasa Di Pura Ulun Danu Batur - I Nengah Ardika (Jayapangus Press, 2018)
The uniqueness of the implementation of Maprani ceremony is held every once a year that is on Ngusabha Kadasa or Ida Bhatara Turun Kabeh and carried out by eating together in the central courtyard (Jaba Tengah). In addition, before the meal together, the ceremony begins with the performance of Titi Swara, which is one of the elders of the adat giving a discourse on susila and tattwa related to life. After Titi Swara coupled with the staging of various types of sacred dance then proceeded by exchanging the banten that was dedicated by a meal with nunas paican Ida Bhatara.